Bacterial vaginosis (BV) and Trichomonas vaginalis (TV) co-infection, and bacterial antibiogram profile of pregnant women studied in Lagos, Nigeria - Christian Azubike Enwuru; Adenike Shola Aiyedobgon; Morakinyo Bamikole Ajayi; Kazeem Adewale Osuolale (BMC, 2024)
Abstract Aim This study was undertaken to determine the prevalence of Bacterial Vaginosis (BV), Trichomonas Vaginalis (TV) co-infection, and the antibacterial sensitivity profile of bacterial isolates. Methods The study was a cross-sectional study of 232 pregnant women on a routine antenatal visit between April 2019 and Sept. 2020, at Amukoko clinic in Lagos, Nigeria. The gynaecologist conducted the clinical examination on each patient looking for vaginal discharge and its consistency/homogeneity, colour and odour. Two High Vaginal Swab (HVS) samples were taken from every patient and a semi-structured questionnaire was used to gather the socio-demographic, practices/attitudes, and clinical information of each participant. One sample was employed for wet preparation to identify the TV and BV diagnosis using Amsel's criteria and Whiff's test. The second sample was used for bacterial culture and antibiogram was conducted using the disc diffusion technique. The Clinical Laboratory Standard Institutes' (CLSI) interpretative criteria were used to categorise the results. Results The mean age of the clients was 28.11 ± 7.08 years of age. The majority (88%) were aged 15-35 years. Only 81 (34.9%) had microbial organisms isolated or seen from their specimens and 19 (8.2%) of such were classified as having BV (Bacteriods or Gardnerella isolated). Of the 81 infected, 33 (40.8%) had only bacterial infection, 36 (44.4%) had TV alone and 12 (14.8%) had bacteria co-infected with TV. From the clinical records, the population that was classified as having UTI or vaginitis was only 46 (20.7%) The study observed age (15-35 years) related association between vaginosis/ TV co-infection (X2 = 7.9; P = 0.005). Participants with symptoms of vaginitis or UTI (mainly E. coli & pseudomonas spp. isolated), BV/co-infection with TV significantly associated with female traders (X2 = 8.5; P = 0.003) and were more associated with those from polygamous relationships (X2 = 18.79, P = 0.0001). Women in their 3rd and 2nd. trimester were more significantly associated with vaginal infection (X2 = 9.47, P = 0.002; X2 = 4.79, P = 0.029) respectively. The Pseudomonas showed susceptibility to ciprofloxacin (CIP) and cefuroxime (CXM). While, E. coli isolates were susceptible to cefepime, ciprofloxacin, and imipenem. Conclusion There is a relatively low prevalence of BV and flagellate co-infection in the community studied. Recommendation We recommend screening of antenatal women with underlying symptoms for BV and flagellates co-infection to avoid its progression to vaginitis.